Pentingnya Izin PIRT Bagi UMKM : Literature Review Articel - Dewi Rahmawati; Marthy Meliana; Windi Tri Wahyuni; Ismatun Maulidiyah; Elsa Saqila; Sirojul Eilma; Ni’matul Fauziah; Brelianty Nevy; Miftahul Maulidiyah; Silvia Nur Diana; Annisya San Shabira; Marselinus Seran; Findy Lovirna (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Home Industry Food or what is abbreviated as PIRT, is a certification for industries that produce food and beverages on a home scale. PIRT certification is only given to processed food products with a low level of risk. Home Industry Food (P-IRT) is a distribution permit for home-scale food production. So that consumers (MSMEs) who want to trade or sell no longer need to worry about dosage, product composition and packaging because safety is guaranteed through a P-IRT certificate or halal certificate. The purpose of making this Literature Review Article is to find out about pirt regulations and the importance of pirt permits for a product. The method used in this article is a literature review method with a literature search based on several literature regarding regulations and PIRT certification permits. The results obtained are understanding the regulations that exist in PIRT for MSME products for consumers so that they can guarantee that these products are not illegal and can be trusted in the eyes of the public. In conclusion, from these reviews, it can be concluded that distribution permits and PIRT certificates are mandatory for MSMEs that sell various kinds of products and know the PIRT regulations.